2014
DOI: 10.1097/prs.0000000000000427
|View full text |Cite
|
Sign up to set email alerts
|

Genome Editing of Mouse Fibroblasts by Homologous Recombination for Sustained Secretion of PDGF-B and Augmentation of Wound Healing

Abstract: These data support that site-specific genome editing allows for sustained cell-based cytokine delivery. Furthermore, sustained release of PDGF-B increases the speed and quality of wound healing after a single application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…11,12 PDGF-B has been widely used for injury healing augmentation as a result of its biological effect. 13 During the current study, PDGF-B overexpression was demonstrated to accentuate the positive effect exerted by BMSCs on TB healing in a rotator cuff repair rat model.…”
mentioning
confidence: 67%
“…11,12 PDGF-B has been widely used for injury healing augmentation as a result of its biological effect. 13 During the current study, PDGF-B overexpression was demonstrated to accentuate the positive effect exerted by BMSCs on TB healing in a rotator cuff repair rat model.…”
mentioning
confidence: 67%
“…Previous work has shown that isolated dermal fibroblasts exhibit enhanced proliferation and migration in the presence of PDGF ligands. 8 10 After skin injury, application of PDGF accelerates the rate of skin wound closure, 11 13 and as such, has been utilized clinically for treatment of ulcerative wounds. 14 16 Conventional Pdgfrα null mice exhibit robust skin defects including dermal hypoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…The double-strand break was repaired by the mammalian cells' native DNA repair mechanism, viz., homologous recombination. These edited fibroblasts persisted in the wound bed for up to 5 months (106).…”
Section: Viral Vector-based Gene Delivery Systemsmentioning
confidence: 99%